Buckling behaviour of underwater vessels by experimental, numerical and analytical approaches - Govindaraj, Moorthy; Murthy, HN Narasimha; Patil, Shivkumar; K., Sudarsan; O.R, Nandagopan; K., Ajith Kumar; Munishaiah, Krishna (Journal of Naval Architecture and Marine Engineering, 2014)
This paper reports the buckling behaviour of glass/vinylester polymer composite filament wound shells of underwater vessels. The shells were tested for buckling under hydrostatic loading and microstrains as a function of applied hydrostatic pressure were measured. Numerical analysis was performed for critical buckling pressure based on Block Lancoz buckling analysis and for Von-Mises stresses and strains based on static analysis using ANSYS. Von-Mises stresses corresponding to hydrostatic pressures were computed analytically by Reduced Stiffness Matrix method. The numerical results of critical buckling pressure for 10 mm thick vessels showed 7.12 % deviation from the experimental results. The microstrains predicted by FEA were in good agreement with the experimental strains. Von-Mises stresses predicted by FEA agreed well with the analytical computations. DOI: http://dx.doi.org/10.3329/jname.v11i1.16087